Fructose and Its Impact on Uric Acid Levels in Humans: A Systematic Review and Meta-Analysis of Clinical Trials from PubMed Database - Baharuddin, Baharuddin; Handayani, Lilies (Politeknik Kesehatan Kemenkes Jakarta II, 2024)
Worldwide fructose consumption continues to increase annually. It is well-established that high-dose fructose consumption can lead to metabolic disorders in humans. One of the indicators affected is uric acid, with several studies reporting increased uric acid levels following fructose intake. This study employs a systematic literature review and meta-analysis approach. We conducted a literature search exclusively in the PubMed database using keywords related to hyperuricemia, uric acid, fructose, and human health. The search was based on the PICO strategy: human health (population), fructose (intervention), glucose (comparison), uric acid (outcome). Nine eligible documents were analyzed for meta-analysis out of 81 documents retrieved from the PubMed database. Based on the Random Effects model (RE), the Standardized Mean Difference (SMD) value was -0.37 (95% CI; -1.34 to 0.59). The RE value crosses the vertical 0 line. Across various clinical studies, fructose consumption did not significantly show negative effects. Although some studies demonstrated dynamic changes, they remained within the normal range. However, these conclusions cannot be directly generalized due to limited knowledge on the long-term effects of fructose. Additionally, aspects such as dosage, duration, type of fructose, anthropometry, and subject characteristics need further attention and analysis in each fructose-related study, as they may be significant factors contributing to variations in study outcomes.